Cien Zawiszy : ostatnie lata marszalka Edwarda Smiglego-Rydza - Wysocki, Wieslaw Jan. (Komorow : Wydawn. Antyk, Marcin Dybowski, 1991)
The last years of Marshal Rydz are recounted here as a final biography.
Includes bibliographical references (p. [115]-132).
Keywords: Rydz-Smigly, Edward, -- 1886-1941.; Poland. -- Armia -- Biography; Marshals -- Poland -- Biography; Statesmen -- Poland -- Biography; Poland -- History -- 1918-1945.